Strategies for Asia Pacific beyond the crisis - Lasserre, Philippe (Macmillan Press, 1999)
This unique book stresses the importance of the Asia Pacific region in the context of the international strategies of the firm. It argues that the crisis in Asia - while being serious - is a temporary phenomenon only and that the need remains for Western firms to boost their position both in Asia and against Asian competition. This requires an increased understanding of Asian markets, Asian firms and Asian business cultures and logic. The authors advise Western firms to approach their operations in Asia strategically, both in terms of competing for customers and resources, as well as co-operating in joint ventures and alliances. They encourage managers to question many of their traditional Western business assumptions and to move towards a regional organisation and a more regional style of management.